Fruit and vegetable processing : improving quality - Jongen, W. M. F. (Woodhead Publishing in food science and technology., 2002)
Fruit and vegetables are both major food products in their own right and key ingredients in many processed foods. There has been growing research on their importance to health and techniques to preserve the nutritional and sensory qualities desired by consumers. This major collection summarises some of the key themes in this recent research. Part one looks at fruit, vegetables and health. There are chapters on the health benefits of increased fruit and vegetable consumption, antioxidants and improving the nutritional quality of processed fruits. Part two considers ways of managing safety and quality through the supply chain. A number of chapters discuss the production of fresh fruit and vegetables, looking at modelling, the use of HACCP systems and ways of maintaining postharvest quality. There are also two chapters on instrumentation for measuring quality. Two final chapters look at maintaining the safety and quality of processed fruit and vegetables. Part three reviews technologies to improve fruit and vegetable products. Two chapters consider how to extend the shelf-life of fruits and vegetables during cultivation. The following three chapters then consider how postharvest handling can improve quality, covering minimal processing, new modified atmosphere packaging techniques and the use of edible coatings. Two final chapters discuss two major recent technologies in processing fruit and vegetables: high pressure processing and the use of vacuum technology. With its distinguished editor and international team of contributors, Fruit and vegetable processing provides an authoritative review of key research on measuring and improving the quality of both fresh and processed fruits and vegetables. Reviews recent research on improving the sensory, nutritional and functional qualities of fruit and vegetables, whether as fresh or processed productsExamines the importance of fruits and vegetables in processed foods and outlines techniques to preserve the nutritional and sensory qualities desired by consumersDiscusses two major technologies in processing fruits and vegetables: high pressure processing and the use of vacuum technology.